Pelaksanaan Tugas dan Fungsi Legislasi Dewan Perwakilan Rakyat Republik Indonesia Periode 2019-2024 - Erminilda Febriani Angkang; Rafael Rape Tupen; Hernimus Ratu Udju (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the implementation of the legislative duties and functions of the House of Representatives of the Republic of Indonesia (DPR RI) during the 2019–2024 period. Legislative function, as stipulated in Article 20A of the 1945 Constitution of the Republic of Indonesia, constitutes one of the core and most influential functions of the DPR, enabling it to affect various aspects of national governance. However, in practice, this function has not been carried out optimally. Legislative performance is evaluated not only in terms of the quantity of legislation produced but also in the quality of the laws enacted. Using a normative juridical research method, grounded in positivist legal theory. The findings indicate that throughout the 2019–2024 period, the DPR’s legislative performance has fluctuated and remained suboptimal. Of the 256 bills included in the National Legislative Program (Prolegnas), only 63 were enacted into law. Several inhibiting factors were identified, including the competency of members, lengthy decision-making procedures, political party composition, and limited public participation. This study underscores the importance of enhancing the capacity of DPR members through regular training and education. Greater transparency in the legislative process is also crucial to maintaining public trust. Furthermore, streamlining bill deliberation mechanisms and fostering inter-factional dialogue are essential strategies to accelerate consensus and improve legislative outcomes.